Antifungal Effect of Brassica Tissues on the Mycotoxigenic Cereal Pathogen Fusarium graminearum - Samina Ashiq; Simon Edwards; Andrew Watson; Emma Blundell; Matthew Back (MDPI AG, 2022)
Fusarium graminearum is a globally important cereal pathogen, causing head blight in wheat, resulting in yield losses and mycotoxin contamination. Currently, triazole fungicides are used to suppress Fusarium graminearum, however, the declining effectiveness of triazoles and concerns over the safety of pesticides have led to the pursuit of safe alternative crop protection strategies such as biofumigation. In the present study, species belonging to Brassicaceae (Brassica juncea, Raphanus sativus, Eruca sativa) were assessed for their biofumigation potential against F. graminearum and the glucosinolate profile of the brassicas was determined. In Petri dishes, mycelial plugs of Fusarium graminearum were exposed to frozen/defrosted leaf discs of brassicas collected at early-leaf, stem-extension, and early-bud stages. Additionally, F. graminearum inoculum was incubated in soil amended with chopped tissues of brassicas in a closed jar experiment. Glucosinolate analysis of the leaf tissue of brassicas revealed that the total glucosinolate concentration of B. juncea 'Brons' increased with advancing growth stage (24.5-51.9 µmol g−1). Brassica juncea leaf discs were effective against mycelial growth, while the sinigrin content in the leaf tissue corresponded to the level of suppression. At the stem-extension and early-bud stages, B. juncea 'Brons' showed 87-90% suppression with four leaf discs, and 100% suppression with eight leaf discs. Brassica juncea 'Caliente Rojo' leaf discs collected at the stem-extension stage showed 94% inhibition with eight discs. In the closed jar experiment, each brassica species significantly suppressed F. graminearum inoculum by 41-55%. The findings suggest that the brassica species investigated in the present study could be effective in reducing the inoculum of F. graminearum in soil prior to cereal production.